2018
DOI: 10.1016/j.cedpsych.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional comparisons: How academic track students’ achievements are related to their expectancy and value beliefs across multiple domains

Abstract: In the present study, we investigated how students' expectancies and values can be predicted by their achievements in multiple domains. Our major aim was to extend previous findings on dimensional comparison processes for expectancies to task values while systematically comparing multiple value facets defined in expectancy-value theory. We assessed the expectancies, values, and achievements of N = 857 students in Grades 5-12 from two German academic track schools in five academic domains. The results for stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
84
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(114 citation statements)
references
References 61 publications
(134 reference statements)
13
84
0
10
Order By: Relevance
“…For example at Wave 1 the correlations between the four variables ranged from R = -.29, p = <.001 (attainment value and inertia) to R = .58, p = <.001 (disinterest and futility), with the average correlation statistic being .45. This finding supports the work of other researchers who have also analyzed task-values using sub-scales for each construct, similarly finding that the sub-scales differentiate in CFA and correlational analyses (Gaspard, Wigfield, Jiang, Nagengast, Trautwein & Marsh, 2018).…”
Section: Descriptive Statisticssupporting
confidence: 89%
“…For example at Wave 1 the correlations between the four variables ranged from R = -.29, p = <.001 (attainment value and inertia) to R = .58, p = <.001 (disinterest and futility), with the average correlation statistic being .45. This finding supports the work of other researchers who have also analyzed task-values using sub-scales for each construct, similarly finding that the sub-scales differentiate in CFA and correlational analyses (Gaspard, Wigfield, Jiang, Nagengast, Trautwein & Marsh, 2018).…”
Section: Descriptive Statisticssupporting
confidence: 89%
“…For instance, high performance in the verbal domain sets a high standard against which students compare their math performance; consequently, students' verbal performance negatively affects their ASC in math, and vice versa, when performance in the same domain is controlled for (for a meta-analysis, see M€ oller, Pohlmann, K€ oller, & Marsh, 2009). Furthermore, several studies have shown that these negative cross-domain comparisons can affect students' intrinsic values as well (e.g., Gaspard et al, 2018;Nagy et al, 2008) and that students' ASCs in math and verbal domains negatively predict each other over time (e.g., Niepel, Brunner, & Preckel, 2014). These negative relations become evident after the early school years (M€ oller et al, 2009;Weidinger, Steinmayr, & Spinath, 2019), likely resulting in increasing intraindividual differentiation in both ASCs and intrinsic values over time.…”
Section: Theoretical Framework: Evt and Dimensional Comparison Theorymentioning
confidence: 99%
“…Researchers using variable‐oriented approaches (e.g., regression, structural equation modeling, and correlation analysis) have demonstrated the unique relations of competence beliefs, task values, and perceived costs to various outcomes in STEM disciplines (e.g., Bathgate, Schunn, & Correnti, ; Bryan, Glynn, & Kittleson, ; Gaspard et al, ; Guo et al, ; Lauermann, Tsai, & Eccles, ; Perez et al, ; Watt et al, ). In a recent example, Lauermann et al () found that math competence beliefs (self‐concept of ability), math utility value, and math interest value in ninth grade were related to ninth‐grade math‐related career plans.…”
Section: Introductionmentioning
confidence: 99%